High force compression mode to Shear mode piezoelectric energy harvesting - Crawley, Fergus J. E.; Luo, Zhenhua (Elsevier, 2024)
This study is to develop structures with the ability to convert a compression force into radial extension or shear force, to increase power output through piezo shear mode. In this work, a piezoceramic-spring system was developed with two types of force-spreading spring configurations, the Belleville disc springs and the crinkle washer. A force loading profile is applied to a piezoceramic element and structure causing the force to be distributed in different directions when compared to a conventional helical spring damping system or compression. The performances of these novel structures were studied using Multiphysics simulation and experiments. This work shows that both the Belleville disc and crinkle washer produce improved energy output between 15 and 22% compared to compression alone, whilst the Belleville disc spring outperformed a crinkle washer in both simulations and experiments. The results show that converting compression to shear force in energy harvesting could be a potential approach to increase the energy efficiency and energy density.
Keywords: Wave; Belville; Crinkle; Washer; Shear; Piezo; Piezoelectric; Energy harvester; Piezo energy harvesting